Glyphosate hormesis attenuates water deficit stress in safflower (Carthamus tinctorius L.) by modulating physiological and biochemical mediators - Camilo dos Santos, Jania Claudia [UNESP]; Ribeiro Silva, Dayane Mércia [UNESP]; Jardim Amorim, Deoclecio; do Rosário Rosa, Vanessa [UNESP]; Farias dos Santos, Anna Luiza [UNESP]; Domingues Velini, Edivaldo [UNESP]; Carbonari, Caio Antonio [UNESP]; de Almeida Silva, Marcelo [UNESP] (Elsevier, 2022)
Changes in photosynthetic machinery can induce physiological and biochemical damage in plants. Low doses of glyphosate have been shown to exert a positive effect in mitigating the deleterious effects of water deficit in plants. Here, the physiological and biochemical mechanisms of safflower plants (Carthamus tinctorius L.) were studied under conditions of water deficit mediated by the attenuating effect of low-dose glyphosate. The plants were divided into two groups of water regimes in soil, without water deficit (−10 kPa) and with water deficit (−70 kPa), and were exposed to different concentrations of glyphosate (0, 1.8, 3.6, 7.2, 18, 36, 72, 180, 360, and 720 g a.e. ha−1). Evident protective responses at the physiological and biochemical levels were obtained after applying low doses of glyphosate to plants under water deficit, with a limiting dose for the occurrence of hormesis (LDS) = 72 g a.e. ha−1. The water deficit in plants resulted in hydrogen peroxide (H2O2) accumulation and consequently lipid peroxidation (LPO) associated with the accumulation of shikimic acid and glyphosate in plants, which triggered an increase in the activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) that act by dismuting the levels of reactive oxygen species (ROS), maintaining, and/or increasing the maximum quantum efficiency of photosystem II (Fv/Fm), effective quantum yield of photosystem II (ΦPSII), electron transport rate (ETR), photochemical extinction coefficient (qP), and non-photochemical extinction coefficient (NPQ). APX appears to be the main enzyme involved in eliminating H2O2. Low doses of glyphosate act as water deficit ameliorators, allowing the plant to maintain/increase metabolism at physiological and biochemical levels by activating antioxidant enzymes in the dismutation of ROS in safflower plants.
Keywords: Chlorophyll fluorescence components; Low dose; N-(phosphonomethyl)glycine; Oilseed; Oxidative stress; Shikimate